Correction: Unveiling the helicity switching mechanism of a rigid two-tiered stacked architecture. Issue 9 (7th February 2019) - Liu, Peng; Duan, Yafei; Bian, Xihui; Tan, Xiaoyao
Abstract : Correction for 'Unveiling the helicity switching mechanism of a rigid two-tiered stacked architecture' by Peng Liu et al., RSC Adv., 2019, 9, 1501–1508.